Essay on Observing Gender Through the Prism of Judith Butler’s Performativity Theory - Sporea, Danijel G. (Collection of Papers of the Faculty of Philosophy in Priština, 2026)
The observation of gender in postmodern discourse has opened the question of conceptuality, with the significant premise that gender is not constant but is continuously changing. When it is said that gender is culturally shaped, it implies its formation on a particular social and cultural basis. From this point of view, gender becomes a sort of ‘achieved status’, i.e. something constructed not only by cultural and social but also by psychological means. More precisely, gender is established, created, or manifested; as a result of everyday interactions in the socialization process, it is repeated, ultimately structuring itself. The starting point for this work is the philosophical opinion of the famous author Judith Butler who, while analysing gender on a theoretical level in her work The Gender Trouble, ‘established’ the outline of the theory of performativity. Hence, one of the goals of this work is the analytical and critical consideration of the thesis of gender as a performative. Judith Butler’s understanding of gender stems from the postulate that “no one is gender from the very beginning” and, actually, “your behaviour creates your sex”, i.e. creates the outlines of gender as a performative. In this context, one can state that gender, as a result of its compulsion, becomes unstable over time. The development of gender in the theory of performativity—a simple linguistic convention that forces us to behave differently, although by doing so, we are aware that in some way we are re-performing or creating gender—opens up space for the analysis of our discourse on gender in a symbolic-discursive order.
Keywords: gender; sex; gender–performative; deconstruction; Judith Butler; The Gender Trouble; performativity theory